Laser metal additive manufacturing study of Fe-based amorphous alloys - Siddiq, Jasmine (Nanyang Technological University, 2024)
High-speed laser metal deposition (HS-LMD) employs a focused laser to melt and deposit metallic powders, creating components with complex geometries and enhanced mechanical properties. This process is particularly effective for Fe-based bulk metallic glasses (BMGs), which are notable for their exceptional strength, corrosion, and wear resistance.